Delineasi Sebaran Sesar di Segmen Cihideung, Sesar Lembang Berdasarkan Metode Fault Fracture Density (FFD) - Tristin Yosefa; Supriyadi Supriyadi; M. Syirojudin; Yosi Setiawan (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2026)
This study aimed to delineate the distribution of faults and fractures in the Cihideung Segment using the Fault Fracture Density (FFD) method based on high-resolution LiDAR topographic data from BMKG in 2024. The LiDAR-based Digital Elevation Model (DEM) data were processed into multi-azimuth hillshade images, followed by visual interpretation of morphological lineaments digitized as polylines. The density of lineament lengths was then calculated within specific grid units to generate an FFD map for identifying structural deformation zones. The results indicate several zones with high lineament density that follow the main trace of the Lembang Fault and its associated branches, particularly around Cihanjuang Rahayu, Cigugur Girang, Gudangkahuripan, and Pagerwangi. These zones are interpreted  as  areas  experiencing  the  most intensive deformation and therefore have important implications for spatial planning, earthquake hazard mitigation, and landslide risk management in the study area. Keywords: LiDAR, Fault Identification, Lineament, Tectonic Geomorphology, Drone, Digital Elevation Model